2005
DOI: 10.1002/bjs.4881
|View full text |Cite
|
Sign up to set email alerts
|

Randomized clinical trial of pylorus-preserving duodenopancreatectomy versus classical Whipple resection—long term results

Abstract: Both procedures were equally effective for the treatment of pancreatic and periampullary cancer. Pylorus-preserving Whipple resection offers some minor advantages in the early postoperative period, but not in the long term.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
147
4
9

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 246 publications
(168 citation statements)
references
References 34 publications
7
147
4
9
Order By: Relevance
“…Overall quality of life was shown to be similar in patients undergoing pylorus-preserving PD and classic Whipple procedure (34,35,37). Moreover, appetite and weight were better preserved in the pylorus-preserving group (34,35).…”
Section: Limitations Of Evidencementioning
confidence: 96%
See 2 more Smart Citations
“…Overall quality of life was shown to be similar in patients undergoing pylorus-preserving PD and classic Whipple procedure (34,35,37). Moreover, appetite and weight were better preserved in the pylorus-preserving group (34,35).…”
Section: Limitations Of Evidencementioning
confidence: 96%
“…With the growing recognition of evidence-based surgery, randomized controlled trials (RCTs) comparing both procedures emerged, followed by systematic reviews and meta-analyses summarizing the existing literature (31)(32)(33). Between 1998 and 2015, eight RCTs comparing both procedures in patients with pancreatic and periampullary carcinoma were published ( Table 1) (20)(21)(22)(34)(35)(36)(37)(38). A currently updated Cochrane review, gives an excellent summary and critical appraisal of the existing evidence (39).…”
Section: Postoperative Morbidity Mortality and Survivalmentioning
confidence: 99%
See 1 more Smart Citation
“…Though some randomized controlled trials (RCTs) and meta-analyses have suggested that these two procedures are comparable in terms of postoperative complications, long-term survival rates and quality of life, other studies have reported that PPPD is superior to classic Whipple's pancreaticoduodenectomy as it results in less occurrence of dumping, diarrhoea and bile reflux gastritis. [3,4] Hence PPPD is claimed to provide the patients with an improved nutritional status. [5,6] However, during the last few decades, significant advances have been made in the understanding of the pathogenesis of periampullary neoplasms.…”
Section: Introductionmentioning
confidence: 99%
“…Postoperative mortality after PD has decreased to below 5% in the past 10 -15 years [6]- [8]. However, mortality is still high, and overall morbidity, including that from pancreatic fistula, delayed gastric emptying, intra-abdominal bleeding, and intra-abdominal abscess, has remained high, ranging from 30% -60% [9]- [11]. In particular, pancreatic fistula still occurs in 5% to 40% of patients [11]- [13], and delayed gastric emptying occurs in 22% to 52% of patients undergoing PD [14] [15] despite refinements in surgical techniques and methods of perioperative management.…”
Section: Introductionmentioning
confidence: 99%